Antibacterial activities and diversity of marine fungi associated with seagrasses collected from Lubang Island, Occidental Mindoro - Dizon, Dianne L.; Dela Cruz, Thomas Edison E. (2011)
Marine fungi are commonly tapped for the production of novel secondary metabolites. However, in the Philippines, very few studies explore marine fungi associated with seagrasses in spite of the numerous species of seagrasses found in the country. Our research study assessed the diversity and antibacterial activities of marine fungi (MF) associated with decaying and healthy seagrass leaves collected from Lubang Island, Occidental Mindoro. A total of 61 MF strains belonging to 15 morphospecies were isolated from surface-sterilized leaf explants inoculated on Potato Carrot Agar supplemented with 33 g/L marine salts and antibiotics. Morphocultural and molecular characterization identified the MF isolated as belonging to the genera Aspergillus, Fusarium, Cladosporium, and Penicillium. Assessment of species diversity showed highest value in the host seagrass Thallasia hemprichii, though, highest species richness was noted in Cymodocea rotundata. Cluster analysis resulted in the grouping of MF based on their host seagrass. Then, 15 MF morphospecies were grown on PDA for the production of secondary metabolites. The crude culture extracts were tested for their antibacterial activities using paper disc diffusion assay. Our result showed that only one isolate, Penicillium sp. 1 exhibited inhibitory activities against extended spectrum beta-lactamase (ESβL)-producing and non-ESβL stains of E. coli and K. pneuminodae while five MF strains exhibited inhibitory activities against S. aureus. The antibacterial activities though were considered as weak. Five MF were then grown on five different media and their crude culture extracts tested against ESβL(+) strains of K. pneumoniae and E. coli using the microtiter plate assay. Results showed that two morphospecies of Penicillium grown on four media exhibited the lowest MIC and MBC values between 7.14 to 71.43 mg/mL. Interestingly, cultivation of MF isolates on a different culture medium resulted in the production of bioactive secondary metabolites as observed in one morphospecies of seagrass-associated Penicillium.
Keywords: Seagrasses; Marine fungi